Sarcasm in Digital Discourse: Representation of Public Distrust of Political Institutions on Patinews Facebook Account - Lukman Alfaris; Nova Khairul Anam; Saeful Rohman; Leli Triana (Jurnal Sastra Indonesia, 2026)
Social media has evolved into a digital public space where people can express opinions, criticism, and dissatisfaction about various political issues. One widely used form of expression is sarcasm, namely the use of sharp, demeaning language to criticize individuals and institutions. This study aims to describe the forms of sarcasm and reveal the representation of public distrust of political institutions in netizen comments on the Patinews Facebook account. The study used a qualitative approach, employing digital discourse analysis and Norman Fairclough's Critical Discourse Analysis framework. The research data consisted of netizen comments on the Patinews post entitled "The DPRD, Kemanakah Disaat Rakyat Membutuhanmu?" published on August 12, 2025. Of the 1,607 available comments, 16 that contained elements of sarcasm were selected using purposive sampling. The results showed that sarcasm was represented in four main forms: negative labeling, distrust, calls for rejection, and comparative satire. The most dominant form is negative labeling, characterized by expressions such as "dagelan," "mafia," "small change," and "party officials" used to describe political institutions. Research findings indicate that sarcasm not only functions as a linguistic strategy to convey criticism, but also represents disappointment, a legitimacy crisis, and declining public trust in political institutions. Furthermore, sarcasm has evolved into a form of symbolic resistance used by society to oppose political practices deemed unfavorable to the people. This research contributes to the study of digital linguistics and discourse by demonstrating that sarcasm is a discursive practice closely related to power relations and democratic dynamics in the digital public sphere.